Integrated high-barrier packaging material and preparation method thereof

By designing integrated high-barrier packaging materials, using the combination of gas barrier layers and other multifunctional layers, the problems of easy oxidation of copper-based conductors and insufficient performance of single-glass components in photovoltaic cells are solved, effectively blocking and protection are achieved, extending the service life of the components and improving reliability.

CN119529694AInactive Publication Date: 2025-02-28ZHEJIANG SINOPONT TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510091266.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The copper-based conductors in photovoltaic cells are prone to oxidation, resulting in reduced conductivity or failure. The water vapor barrier performance of single glass components is insufficient, the stress management is poor, the bonding reliability is poor, and the heat dissipation performance is limited, which affects the long-term performance stability of the components.

Method used

An integrated high-barrier packaging material is designed, including an adhesive packaging layer, optical management layer, gas barrier layer, mechanical transition layer and insulating support layer. The design of the gas barrier layer achieves low oxygen transmittance. Other layers help improve barrier properties while achieving multifunctional compatibility and protect the copper material from oxidation.

Benefits of technology

Effectively protect copper materials from oxidation, extend the service life of the module, improve the long-term performance stability and reliability of photovoltaic modules, and shorten the component lamination process time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529694A_ABST
    Figure CN119529694A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic packaging materials, and discloses an integrated high-barrier packaging material and a preparation method thereof.The integrated high-barrier packaging material comprises a bonding packaging layer, a light management layer, a gas barrier layer, a mechanical transition layer and an insulating supporting layer which are sequentially arranged, and the packaging material is obtained through integrated multi-layer co-extrusion; a resin system adopted by the gas barrier layer is high-barrier resin; the first melting point of the bonding packaging layer is 70-100 DEG C, and the second melting point of the bonding packaging layer is 110-130 DEG C; the melting point of the light management layer is 70-130 DEG C; the melting point of the gas barrier layer is 170-190 DEG C, and the oxygen permeability is lower than 0.5 cm < 3 >. M <-2 >. Day <-1 >. Atm <-1 >; the melting point of the mechanical transition layer is 90-130 DEG C; and the melting point of the insulating support layer is 120-180 DEG C. The gas barrier layer in the packaging material disclosed by the invention has excellent barrier performance, and the sensitivity of copper paste to an oxidation environment is relieved, so that the long-acting conductivity of a photovoltaic cell is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic packaging materials, and in particular to an integrated high-barrier packaging material and a preparation method thereof. Background Art

[0002] Silver paste in photovoltaic cells is widely used due to its conductivity and stability, but its high cost limits the industry's need to further reduce costs and increase efficiency. In order to reduce costs, silver-coated copper paste or pure copper paste has become a potential alternative. However, the chemical properties of copper determine that it is susceptible to oxidation and corrosion. The copper oxide or copper ion migration produced after copper oxidation will reduce the conductivity and photoelectric conversion efficiency of the battery, and even cause failure problems, directly threatening the long-term performance stability of photovoltaic cells.

[0003] At the same time, although single-glass structure modules have the advantages of light weight and easy processing, in recent years, with the promotion of silver-free paste batteries (such as copper-based conductor batteries), single-glass modules face the following challenges: (1) Oxidation problems caused by low barrier properties: Copper-based conductors are more easily oxidized, and the water vapor barrier properties of the single-glass module backplane cannot effectively protect the conductive layer, resulting in decreased conductivity or failure; (2) Insufficient stress management: The mechanical properties of the single-glass module backplane are weak, and it is difficult to relieve the mechanical stress generated by battery cell welding and thermal cycling, which may lead to hidden cracks or failure; (3) Bonding reliability: The bonding performance and chemical stability of the backplane are insufficient, which may cause interface problems with silver-free paste batteries during long-term use, such as copper ion migration caused by electrochemical reactions; (4) Heat dissipation performance limitations: The single-glass module has poor heat dissipation performance, which may cause excessive temperature rise of the battery cell and accelerate performance degradation.

[0004] Therefore, the barrier properties of packaging materials become particularly critical, and excellent barrier layer design must be used to reduce the infiltration of external water vapor and oxygen to prevent copper oxidation. At the same time, packaging materials need to have high mechanical strength and durability to ensure the reliability of photovoltaic modules for long-term outdoor use. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an integrated high-barrier packaging material and a preparation method thereof. The design of the gas barrier layer can play a major barrier effect, has a low oxygen permeability, and can prevent water vapor and oxygen from entering the interior of the packaging material. The other layers can not only achieve multi-functional compatibility, but also assist in improving the barrier performance of the packaging material, thereby effectively protecting the copper material from oxidation and greatly extending the service life of the component. In addition, different types of materials can be co-extruded at high temperatures, shortening the process time of component lamination and improving component reliability.

[0006] The purpose of the present invention is achieved through the following technical solutions: In the first aspect, the present invention provides an integrated high-barrier packaging material, comprising an adhesive packaging layer, a light management layer, a gas barrier layer, a mechanical transition layer and an insulating support layer arranged in sequence, and the packaging material is obtained by integrated multi-layer co-extrusion; the resin system used in the gas barrier layer is a high-barrier resin, and the resin systems used in the other layers include one or more homopolymers and copolymers of ethylene, vinyl acetate, propylene, butene, hexene, and octene; the first melting point of the adhesive packaging layer is 70-100°C, the second melting point is 110-130°C, and the cross-linked gel content after irradiation cross-linking is 5-30%; the melting point of the light management layer is 70-130°C; the melting point of the gas barrier layer is 170-190°C, and the oxygen permeability is less than 0.5cm 3 ·m -2 ·day -1 ·atm -1 ; The melting point of the mechanical transition layer is 90-130℃; the melting point of the insulating support layer is 120-180℃.

[0007] The integrated packaging material of the present invention is provided with a gas barrier layer, which uses a high barrier resin as a resin system. While satisfying good compatibility with other layers, it has a low oxygen permeability and can block water vapor and oxygen from entering the interior of the packaging material, thereby effectively protecting the copper material from oxidation, greatly extending the service life of the component, and meeting the use requirements of the copper paste in harsh environments.

[0008] In addition, while providing adhesion and stress buffering, the bonding encapsulation layer also has certain barrier properties, and can ensure chemical stability to copper-based materials and avoid adverse reactions at the interface. The light management layer is mainly used to reflect light and improve photovoltaic efficiency, but its resin combined with light-reflecting fillers can also play a certain barrier effect, which can further reduce the corrosion of environmental factors (such as ultraviolet rays and water vapor). The mechanical transition layer plays a mechanical buffering role. It connects the gas barrier layer and the insulating support layer to optimize the compatibility between the layers. The insulating support layer has a higher melting point, which not only provides mechanical strength, but also has good electrical insulation, further protecting the conductive properties of the silver-coated copper paste or copper paste from the influence of external electrochemical effects.

[0009] Therefore, the integrated packaging material in the present invention can play a major barrier effect through the design of the gas barrier layer. While achieving multifunctional compatibility, the other layers can also assist in improving the barrier performance of the packaging material. Different types of materials can be co-extruded by cast film at high temperature, which shortens the process time of component lamination and improves component reliability. It can replace the combination of traditional packaging film and photovoltaic backplane.

[0010] Preferably, the resin in the resin system used in each layer (except the gas barrier layer) includes one or more homopolymers and copolymers of ethylene, propylene, butene, hexene, octene, and vinyl acetate, the mass fraction of α-olefin in the copolymer is controlled at 5-20wt%, and the proportion of vinyl acetate as a comonomer is controlled at 18-40wt%.

[0011] Preferably, the resin in the resin system used in each layer (except the gas barrier layer) includes a polar modified resin, which is one or more of homopolymers and copolymers of ethylene, propylene, butene, hexene, octene, and vinyl acetate modified with polar groups. The polar groups include one or more of silane groups, siloxy groups, epoxy groups, maleic anhydride groups, and isocyanate groups.

[0012] Preferably, the resin system used in each layer (except the gas barrier layer) has a melt index of 2-20 g / 10min and a density of 0.850-0.950 g / cm 3 , number average molecular weight is 50,000-250,000, and molecular weight distribution is 2.8-20.

[0013] Preferably, the resin system used for the bonding encapsulation layer comprises, by mass percentage, 5-30 wt % of a low melting point resin, 70-90 wt % of a high melting point resin, and 3-5 wt % of a polar modified resin.

[0014] Preferably, the resin system used in the light management layer comprises, by weight percentage, 5-40 wt % of a low melting point resin, 60-95 wt % of a high melting point resin, and 3-5 wt % of a polar modified resin.

[0015] Preferably, the low melting point resin has a melting point of 70-100° C. and a melt index of 11-20 g / 10 min; the high melting point resin has a melting point of 110-130° C. and a melt index of 3-10 g / 10 min.

[0016] The light management layer uses a resin system similar to that of the bonding encapsulation layer. The melting point of each layer is mainly determined by the melting point of the selected resin system. Therefore, both the light management layer and the bonding encapsulation layer have two melting points, the first melting point is 70-100°C, and the second melting point is 110-130°C.

[0017] Preferably, the resin system used in the gas barrier layer is a high barrier resin.

[0018] By optimizing the blending ratio of polyolefin resin and high barrier resin, the barrier performance is achieved while ensuring the casting processability. By adding polar group modified masterbatch to enhance the interfacial adhesion between the blended components, the barrier properties of the high barrier resin are retained while avoiding the difficulty of processing due to excessive brittleness of the material. In addition, after adding high polarity modified masterbatch, the intermolecular force enhances the density and stability of the layer by introducing physical effects such as hydrogen bonding and polymer chain entanglement, and the barrier performance is significantly improved while maintaining a certain degree of flexibility. Adding acid neutralizing additives can reduce acid erosion on the material and maintain the mechanical strength and long-term performance of the material.

[0019] Preferably, the high barrier resin includes one or more of ethylene-vinyl alcohol copolymer (EVOH, ethylene content controlled at 15-30wt%) and polyvinyl alcohol (PVOH, high hydrolysis degree 99%+).

[0020] Preferably, the melting point of the resin system used in the mechanical transition layer is 90-130° C., including polar modified resin.

[0021] Preferably, the melting point of the resin system used in the insulating support layer is 140-180° C. In terms of mass percentage, the resin system includes 90-95 wt % of a resin having a melting point of 140-180° C. and a melt index of 2-12 g / 10 min.

[0022] Preferably, the bonding encapsulation layer further comprises the following components, based on the proportion of the resin system of the layer: 0.5-4 wt% of a radiation cross-linking agent, 0.5-1 wt% of a coupling agent, 0.5-1 wt% of a UV absorber, 0.2-0.4 wt% of an antioxidant, and 4-40 wt% of a polar group grafted masterbatch.

[0023] Preferably, the light management layer further comprises the following components, based on the proportion of the resin system of this layer: 0.5-1 wt % of coupling agent, 0.5-1 wt % of UV absorber, 0.2-0.4 wt % of antioxidant, 4-7 wt % of light reflective filler and 4-40 wt % of polar group grafted masterbatch.

[0024] Preferably, the gas barrier layer further comprises the following components, based on the proportion of the resin system of the layer: 0.5-5 wt % of UV absorber, 0.5-2 wt % of antioxidant, 0.1-5 wt % of acid absorption aid, 1-10 wt % of plasticizer, 0.5-3 wt % of lubricant and 0-8 wt % of moisture absorption inhibitor.

[0025] Preferably, the mechanical transition layer further comprises the following components, calculated based on the proportion of the resin system of the layer: 0.5-3 wt% of radiation co-crosslinking agent, 0.5-1 wt% of coupling agent, 0.5-1 wt% of ultraviolet absorber, 0.2-0.4 wt% of antioxidant and 0.5-5 wt% of processing aid. The degree of radiation crosslinking of the mechanical transition layer is not specifically specified.

[0026] Preferably, the insulating support layer further comprises the following components, based on the proportion of the resin system of the layer: 0.8-1.5 wt % of a UV absorber, 0.5-2 wt % of an antioxidant, and 0.5-3 wt % of a processing aid.

[0027] Preferably, the thickness of the bonding encapsulation layer is 100-300 μm; the thickness of the light management layer is 100-200 μm; the thickness of the gas barrier layer is 80-150 μm; the thickness of the mechanical transition layer is 20-80 μm; and the thickness of the insulating support layer is 200-300 μm.

[0028] Preferably, the acid absorption aid comprises one or more of alkaline fillers, amine compounds, sulfur-containing compounds and epoxy compounds.

[0029] The alkaline filler includes one or more of calcium carbonate, aluminum hydroxide, magnesium hydroxide and magnesium oxide.

[0030] The amine compound includes one or more of polyethylene polyamine (PEI), triethanolamine (TEA) and a polymer containing an amide group (such as polyvinyl pyrrolidone (PVP)).

[0031] The sulfur-containing compound includes one or more of mercaptan (R-SH) and thioamide compounds.

[0032] Preferably, the plasticizer comprises polyethylene glycol with a molecular weight of 400-800.

[0033] Preferably, the lubricant includes one or more of zinc stearate, stearic acid amide and calcium stearate.

[0034] Preferably, the moisture absorption inhibitor includes one or more of silica gel powder and nano-silicon dioxide.

[0035] Preferably, the radiation cross-linking aid comprises a multifunctional unsaturated monomer, including one or more of multifunctional acrylate, olefin and isocyanate compounds.

[0036] The radiation auxiliary cross-linking agent can generate free radicals under radiation conditions to form cross-links.

[0037] Acrylate compounds: Ethylene glycol dimethacrylate (EGDMA), trimethylolpropane triacrylate (TMPTA), hexanediol diacrylate (HDDA), hexanediol diacrylate (HDDA), pentaerythritol tetraacrylate (PETA, Pentaerythritol Tetraacrylate), pentaerythritol tetramethacrylate (PETMA, Pentaerythritol Tetramethacrylate), triphenylmethane triacrylate (TPMTA, Triphenylmethane Triacrylate), bisphenol A diglycidyl ether diacrylate (Bisphenol ADiacrylate), dipentaerythritol hexaacrylate, polypentaerythritol multiacrylate (DPHA), triethoxysilane acrylate (Acryloxypropyltriethoxysilane, APTES), allyl acrylate, allyl methacrylate, diallyl maleate, diallyl phthalate, allyl acrylate, allyl methacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, ethoxylated glycerol triacrylate, tetramethylolmethane triacrylate, ethoxylated pentaerythritol tetraacrylate, dimethylolpropane tetraacrylate, trimethylolethane trimethacrylate, tetramethylolmethane tetraacrylate, ditrimethylolpropane tetraacrylate, tetramethylolmethane tetramethacrylate, ditrimethylolpropane tetramethacrylate, dipentaerythritol polyacrylate, dipentaerythritol hexaacrylate, dipentaerythritol polymethacrylate, dipentaerythritol hexamethacrylate.

[0038] Olefin compounds: divinylbenzene, di-isopropenylbenzene, diallyl phthalate.

[0039] Isocyanate compounds: trimethallyl isocyanate, triallyl isocyanurate, triallyl cyanurate.

[0040] Preferably, the coupling agent includes one or more of a silane coupling agent, a titanate coupling agent, an isocyanate coupling agent, a phosphorus-containing coupling agent, an epoxy resin coupling agent, a surfactant coupling agent, and an anhydride-modified resin.

[0041] Silane coupling agent: γ-glycidoxypropyltrimethoxysilane (KH-560), vinyltriethoxysilane (VTES), aminopropyltriethoxysilane (KH-550), mercaptopropyltrimethoxysilane (KH-580), 3-glycidoxypropyltrimethoxysilane (3-Glycidoxypropyltrimethoxysilane).

[0042] Isocyanate coupling agent: triisocyanate (such as HDI-Trimer).

[0043] Titanate coupling agent: isopropyl tri(dioctyl phosphate) titanate, tetraisopropyl titanate, di(acetylacetonate) diisopropyl titanate.

[0044] Phosphorus-containing coupling agents: phosphate esters (such as diethylhexyl phosphate), phosphate acrylates (such as ethylene glycol methacrylate phosphate).

[0045] Surfactant coupling agent: quaternary ammonium surfactant, block copolymer surface modifier, fluorinated silane (such as hexafluoropropane trifluoroethoxysilane), nanoparticle composite modifier (such as surface functionalization of nano-silica or alumina (silane or phosphoric acid modification)).

[0046] Anhydride modified resin: maleic anhydride grafted polyolefin (POE-g-MAH), methacrylic acid grafted polyolefin (POE-g-MAA).

[0047] Preferably, the light-reflecting filler includes one or more of nano titanium dioxide, calcium carbonate, zinc barium white, wollastonite, mica powder, magnesium hydroxide, aluminum hydroxide, calcium hydroxide, talc, barium sulfate, glass beads, zinc sulfide, kaolin, montmorillonite, chromium oxide green, vanadium titanium brown, and cerium oxide; and also includes one or more of phthalocyanine blue, diarylethene, and PTFE powder; the particle size distribution is not greater than 1.5 μm.

[0048] Preferably, the UV absorber includes hindered amine light stabilizer HALS (Tinuvin 770, Tinuvin 622, Chimassorb 944), benzotriazole UV absorbers (Tinuvin 234, Tinuvin 326, Tinuvin 327, Tinuvin 328), mixed light stabilizers (Tinuvin 123, Tinuvin 329), benzophenone UV absorbers (UV-209, UV-1009, UV-981, UV-2126), and hydroxybenzophenone UV absorbers (UV-9).

[0049] Preferably, the antioxidant includes one or more of hindered phenol antioxidants (Irganox 1010, Irganox 1076), phosphite antioxidants (Irgafos 168, Ultranox 626), thioester antioxidants (DSTDP, DLTDP), hindered amines (Tinuvin 770, Chimassorb 944), metal passivators (Irgacor 1520, Naugard XL-1), nano additives (ZnO, TiO2), and antioxidant BHT.

[0050] Preferably, the polar group grafted masterbatch comprises a masterbatch made of a resin raw material grafted with a silane group, a siloxy group, an epoxy group, a maleic anhydride group or an isocyanate group.

[0051] Preferably, the processing aid includes one or more of a dispersant, a compatibilizer and an optical modifier.

[0052] In the second aspect, the present invention also provides a method for preparing an integrated high-barrier packaging material, comprising the following steps: after the raw material components of each layer are mixed separately, a multi-layer integrated melt co-extrusion is adopted, the melt extrusion temperature of the bonding packaging layer is 180-200°C, the melt extrusion temperature of the light management layer is 190-220°C, the melt extrusion temperature of the gas barrier layer is 180-220°C, the melt extrusion temperature of the mechanical transition layer is 190-220°C, and the melt extrusion temperature of the insulating support layer is 200-230°C; after extrusion, the cast film is cooled, and then irradiated pre-crosslinked and post-treated in sequence to obtain an integrated high-barrier packaging material.

[0053] Preferably, during casting cooling, the temperature of the cooling roller is 20-30°C.

[0054] Preferably, the film after casting and cooling is subjected to a baking heat treatment, with a baking temperature of ≥70°C and a time of ≥30s to eliminate processing thermal stress, and then irradiated for pre-crosslinking.

[0055] Preferably, the radiation pre-crosslinking is performed by electron beam irradiation, and the irradiation parameters are 150-500kev and 30-60kgy.

[0056] Preferably, the post-processing includes pulling and stretching, winding and reeling.

[0057] Post-processing steps such as pulling, stretching, winding, and coiling can be carried out directly after irradiation pre-crosslinking; or, post-processing steps such as pulling, stretching, winding, and coiling can be carried out after the welding wire is bonded and distributed.

[0058] The film is stretched to control the thickness and mechanical properties.

[0059] Preferably, an antistatic coating may be applied online during post-treatment.

[0060] Compared with the prior art, the present invention has the following beneficial effects: (1) Water vapor and oxygen barrier properties: The excellent barrier properties (low transmittance) of the gas barrier layer directly alleviate the sensitivity of the copper paste to the oxidative environment, allowing the copper-based material to maintain a low corrosion rate in a humid, oxidative environment, thereby maintaining the long-term conductivity of the photovoltaic cell.

[0061] (2) Interface stability: The bonding packaging layer can improve its chemical compatibility with the copper paste, avoid electrochemical instability between the packaging material and the copper paste, and reduce the risk of copper ion migration.

[0062] (3) UV protection and mechanical protection: The light management layer, mechanical transition layer and insulating skeleton layer can effectively block the damage of ultraviolet radiation to the copper paste, while providing sufficient mechanical strength to avoid the intensification of oxidation caused by microcracks or packaging damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is a schematic diagram of the structure of the integrated high-barrier packaging material in Example 1 of the present invention.

[0064] The figures are marked as follows: 1. bonding packaging layer; 2. light management layer; 3. gas barrier layer; 4. mechanical transition layer; 5. insulating support layer. DETAILED DESCRIPTION

[0065] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0066] Bonding encapsulation layer Ⅰ The raw material components of the bonding encapsulation layer I are shown in Table 1, and its first melting point is 75°C and its second melting point is 120°C.

[0067] Table 1

[0068] Bonding encapsulation layer Ⅱ The raw material components of the bonding encapsulation layer II are shown in Table 2, and the first melting point is 85°C and the second melting point is 115°C.

[0069] Table 2

[0070] Optical Management Layer I The raw material components of the photomanagement layer I are shown in Table 3, and its first melting point is 75°C and its second melting point is 120°C.

[0071] Table 3

[0072] Optical Management Layer Ⅱ The raw material components of the photomanagement layer II are shown in Table 4, and its first melting point is 85°C and the second melting point is 115°C.

[0073] Table 4

[0074] Gas barrier layer Ⅰ The raw material composition of the gas barrier layer I is shown in Table 5, and its melting point is 190°C.

[0075] Table 5

[0076] Gas barrier layer II The raw material composition of the gas barrier layer II is shown in Table 6, and its melting point is 190°C.

[0077] Table 6

[0078] Gas barrier layer III The raw material composition of the gas barrier layer III is shown in Table 7, and its melting point is 180°C.

[0079] Table 7

[0080] Gas barrier layer IV The raw material composition of the gas barrier layer IV is shown in Table 8, and its melting point is 170°C.

[0081] Table 8

[0082] Mechanical transition layer I The raw material composition of the mechanical transition layer I is shown in Table 9, and its melting point is 120°C.

[0083] Table 9

[0084] Mechanical transition layer II The raw material composition of the mechanical transition layer II is shown in Table 10, and its melting point is 110°C.

[0085] Table 10

[0086] Insulation support layer Ⅰ The raw material composition of the insulating support layer I is shown in Table 11, and its melting point is 165°C.

[0087] Table 11

[0088] Insulation support layer Ⅱ The raw material composition of the insulating support layer II is shown in Table 12, and its melting point is 160°C.

[0089] Table 12

[0090] Example 1 Integrated high-barrier packaging material: from inside to outside, it includes a 250μm adhesive packaging layer I (whose components are shown in Table 1), a 100μm light management layer I (whose components are shown in Table 3), a 100μm gas barrier layer I (whose components are shown in Table 5), a 50μm mechanical transition layer I (whose components are shown in Table 9) and a 200μm insulating support layer I (whose components are shown in Table 11).

[0091] The preparation of the above packaging material comprises the following steps: The raw material components of each layer are uniformly mixed using a high-speed mixer, and then multi-layer co-extrusion is adopted for melt extrusion. Five extruders are used for separate processing, and the extruder temperatures are set as follows: the melt extrusion temperature of the bonding encapsulation layer is 180-200°C, the melt extrusion temperature of the light management layer is 190-220°C, the melt extrusion temperature of the gas barrier layer is 180-220°C, the melt extrusion temperature of the mechanical transition layer is 190-220°C, and the melt extrusion temperature of the insulating support layer is 200-230°C.

[0092] The five strands of molten materials are gathered to the co-extrusion die through a distributor to form a multi-layer flow channel structure. The molten material is extruded through a wide die and cast onto a cooling roller with a temperature of 30°C for cooling and forming. After that, the pre-crosslinking treatment is performed by electron beam irradiation with irradiation parameters of 200kev and 38kgy. After traction, stretching, winding and reeling, the multi-layer film is reeled online and the thickness uniformity is tested, such as Figure 1 As shown, an integrated high-barrier packaging material is obtained, which includes, from top to bottom, an adhesive packaging layer 1, a light management layer 2, a gas barrier layer 3, a mechanical transition layer 4, and an insulating support layer 5.

[0093] Example 2 Integrated high-barrier packaging material: from inside to outside, it includes a 300μm adhesive packaging layer I (whose components are shown in Table 1), a 120μm light management layer I (whose components are shown in Table 3), a 100μm gas barrier layer II (whose components are shown in Table 6), a 30μm mechanical transition layer II (whose components are shown in Table 10) and a 230μm insulating support layer I (whose components are shown in Table 11).

[0094] The preparation steps and parameter settings of the above packaging materials are the same as those in Example 1.

[0095] Example 3 Integrated high-barrier packaging material: from inside to outside, it includes a 200μm adhesive packaging layer I (whose components are shown in Table 1), a 150μm light management layer I (whose components are shown in Table 3), a 100μm gas barrier layer III (whose components are shown in Table 7), a 50μm mechanical transition layer II (whose components are shown in Table 10) and a 280μm insulating support layer II (whose components are shown in Table 12).

[0096] The preparation steps and parameter settings of the above packaging materials are the same as those in Example 1.

[0097] Example 4 Integrated high-barrier packaging material: from inside to outside, it includes a 250μm adhesive packaging layer II (whose components are shown in Table 2), a 100μm light management layer II (whose components are shown in Table 4), a 120μm gas barrier layer III (whose components are shown in Table 7), a 50μm mechanical transition layer I (whose components are shown in Table 9) and a 200μm insulating support layer II (whose components are shown in Table 12).

[0098] The preparation steps and parameter settings of the above packaging materials are the same as those in Example 1.

[0099] Example 5 Integrated high-barrier packaging material: from inside to outside, it includes a 250μm adhesive packaging layer II (whose components are shown in Table 2), a 100μm light management layer II (whose components are shown in Table 4), a 120μm gas barrier layer IV (whose components are shown in Table 8), a 50μm mechanical transition layer I (whose components are shown in Table 9) and a 200μm insulating support layer II (whose components are shown in Table 12).

[0100] The preparation steps and parameter settings of the above packaging materials are the same as those in Example 1.

[0101] Example 6 Integrated high-barrier packaging material: from inside to outside, it includes a 250μm adhesive packaging layer II (whose components are shown in Table 2), a 100μm optical management layer II (whose components are shown in Table 4), a 50μm mechanical transition layer I (whose components are shown in Table 9) and a 200μm insulating support layer II (whose components are shown in Table 12).

[0102] The preparation of the above packaging material comprises the following steps: The raw material components of each layer are uniformly mixed using a high-speed mixer, and then multi-layer co-extrusion is adopted for melt extrusion. Four extruders are used for separate processing. The extruder temperatures are set as follows: the melt extrusion temperature of the bonding encapsulation layer is 180-200°C, the melt extrusion temperature of the optical management layer is 190-220°C, the melt extrusion temperature of the mechanical transition layer is 190-220°C, and the melt extrusion temperature of the insulating support layer is 200-230°C.

[0103] Four streams of molten material are converged to the co-extrusion die through a distributor to form a multi-layer flow channel structure. The molten material is extruded through a wide die, cast onto a cooling roller with a temperature of 30°C, and cooled to form. After that, electron beam irradiation pre-crosslinking treatment is carried out with irradiation parameters of 200kev and 38kgy. After traction, stretching, winding and reeling, the prepared multi-layer film is reeled online and the thickness uniformity is tested to obtain an integrated high-barrier packaging material.

[0104] Comparative Example 1 Packaging materials: from inside to outside, it includes a pre-cross-linked EVA layer (100μm; its raw materials include 2825 brand EVA particles and 0.5wt% of peroxide initiator, 0.3wt% of acrylic acid cross-linking agent, and 0.3wt% of silane coupling agent accounting for 0.5wt% of the resin raw materials), an encapsulation EVA layer (300μm), and a commercially available CPC photovoltaic backplane (Zhonglai FFC-JW30 (Plus), with a total thickness of 315μm; the structure is coating / PET / coating, and the thickness of PET is 280 μm).

[0105] The above-mentioned layers of materials are laminated to obtain an integrated packaging material, and the lamination parameters are: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 10 minutes.

[0106] Table 13

[0107] Application Example 1 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (welding wires fixed on the battery with UV-curing glue are connected in series, and the battery metallization is low-temperature sintered pure copper paste) / packaging material obtained in Example 1 (the battery contact surface is the surface of the bonding packaging layer).

[0108] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 7 minutes.

[0109] Application Example 2 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (solder wires fixed to the battery with UV-curing glue are connected in series, wherein the battery metallization is high-temperature sintered silver-coated copper paste with a silver content of less than 30 wt %) / packaging material obtained in Example 2 (the battery contact surface is the surface of the bonding packaging layer).

[0110] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 7 minutes.

[0111] Application Example 3 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (solder wires fixed to the battery with UV-curing glue are connected in series, wherein the battery metallization is high-temperature sintered silver-coated copper paste with a silver content of less than 30 wt %) / packaging material obtained in Example 3 (the battery contact surface is the surface of the bonding packaging layer).

[0112] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 7 minutes.

[0113] Application Example 4 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (solder wires fixed to the battery with UV-curing glue are connected in series, wherein the battery metallization is high-temperature sintered silver-coated copper paste with a silver content of less than 30 wt %) / packaging material obtained in Example 4 (the battery contact surface is the surface of the bonding packaging layer).

[0114] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 7 minutes.

[0115] Application Example 5 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (solder wires fixed to the battery with UV-curing glue are connected in series, wherein the battery metallization is high-temperature sintered silver-clad copper paste with a silver content of less than 30 wt %) / packaging material obtained in Example 5 (the battery contact surface is the surface of the bonding packaging layer).

[0116] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 7 minutes.

[0117] Application Example 6 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (solder wires fixed to the battery with UV-curing glue are connected in series, wherein the battery metallization is high-temperature sintered silver-coated copper paste with a silver content of less than 30 wt %) / packaging material obtained in Example 6 (the battery contact surface is the surface of the bonding packaging layer).

[0118] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 7 minutes.

[0119] Application Example 7 The structure of the photovoltaic module is: glass / EVA packaging film / TOPCon technology back-contact 0BB battery (welding wires fixed to the battery with UV-curing glue are connected in series, wherein the battery metallization is high-temperature sintered silver-clad copper paste with a silver content of less than 30wt%) / packaging material obtained in Comparative Example 1 (the battery contact surface is the surface of the pre-cross-linked EVA layer).

[0120] The materials were assembled in the above order to obtain a photovoltaic module, and the photovoltaic module was laminated with the glass side facing downward. The lamination parameters were: temperature of 150° C., vacuuming for 5 minutes, pressure of -20 kPa, and pressure maintenance for 12 minutes.

[0121] Table 14

[0122] As shown in Table 13, the packaging materials for integrated photovoltaic modules prepared in Examples 1-5 can be cast and coextruded at high temperatures, and have better overall performance than the packaging materials prepared in Comparative Example 1. The present invention can simultaneously meet the mechanical properties and bonding properties at the working temperature of the photovoltaic module. Moreover, compared with the packaging materials in Example 6 that do not contain a gas barrier layer, Examples 1-5 significantly reduce the permeability of the packaging materials to oxygen and water vapor. The excellent barrier properties directly alleviate the sensitivity of the copper paste to the oxidizing environment, so that the copper-based material maintains a low corrosion rate in a humid and oxidizing environment, and improves the aging resistance, thereby maintaining the long-term conductivity of the photovoltaic cell, improving the reliability of the component, and achieving the characteristics of multi-functional compatibility.

[0123] As shown in Table 14, the packaging materials in Examples 1-5 and Comparative Example 1 are respectively assembled to obtain photovoltaic modules. From the data comparison between Application Examples 1-5 and Application Example 7, it can be seen that the present invention can shorten the process time of module lamination, and the smaller the power loss of the battery after packaging, the lower the power attenuation rate of the DH3000 test. In addition, the packaging materials in Example 6 are assembled to obtain photovoltaic modules. Since the packaging materials do not contain a gas barrier layer, the power attenuation rate of the DH3000 test of Application Example 6 will also be significantly reduced. Compared with Application Examples 2-5, Application Example 1 uses pure copper paste, which is easier to oxidize than silver-coated copper paste, and thus has a greater power attenuation rate.

[0124] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An integrated high barrier packaging material, characterized in that: The packaging material comprises an adhesive packaging layer, a light management layer, a gas barrier layer, a mechanical transition layer and an insulating support layer which are arranged in sequence, and is obtained by integrated multi-layer co-extrusion; the resin system used in the gas barrier layer is a high barrier resin, and the resin systems used in the other layers include one or more homopolymers and copolymers of ethylene, vinyl acetate, propylene, butene, hexene and octene; The first melting point of the bonding encapsulation layer is 70-100℃, the second melting point is 110-130℃, and the cross-linked gel content after irradiation cross-linking is 5-30%; the melting point of the light management layer is 70-130℃; the melting point of the gas barrier layer is 170-190℃, and the oxygen permeability is less than 0.5cm 3 ·m -2 ·day -1 ·atm -1 ; The melting point of the mechanical transition layer is 90-130℃; the melting point of the insulating support layer is 120-180℃.

2. The integrated high barrier packaging material according to claim 1, characterized in that: The gas barrier layer further comprises the following components, in proportion to the resin system of the layer: 0.5-5 wt % of UV absorber, 0.5-2 wt % of antioxidant, 0.1-5 wt % of acid absorption aid, 1-10 wt % of plasticizer, 0.5-3 wt % of lubricant and 0-8 wt % of moisture absorption inhibitor.

3. The integrated high barrier packaging material according to claim 2, characterized in that: The high barrier resin includes one or more of ethylene-vinyl alcohol copolymer and polyvinyl alcohol; the acid absorption aid includes one or more of alkaline fillers, amine compounds, sulfur-containing compounds and epoxy compounds.

4. The integrated high barrier packaging material according to claim 2 or 3, characterized in that: The plasticizer includes polyethylene glycol; the lubricant includes one or more of zinc stearate, stearic acid amide and calcium stearate.

5. The integrated high barrier packaging material according to claim 1, characterized in that: According to the proportion of the resin system of this layer, the bonding encapsulation layer also includes the following components: 0.5-4 wt% of radiation cross-linking agent, 0.5-1 wt% of coupling agent, 0.5-1 wt% of ultraviolet absorber, 0.2-0.4 wt% of antioxidant and 4-40 wt% of polar group grafted masterbatch.

6. The integrated high barrier packaging material according to claim 1, characterized in that: According to the proportion of the resin system in this layer, the light management layer also includes the following components: coupling agent 0.5-1 wt%, UV absorber 0.5-1 wt%, antioxidant 0.2-0.4 wt%, light reflective filler 4-7 wt% and polar group grafted masterbatch 4-40 wt%.

7. The integrated high-barrier packaging material according to claim 1, characterized in that: According to the proportion of the resin system of this layer, the mechanical transition layer also includes the following components: 0.5-3 wt% of radiation cross-linking agent, 0.5-1 wt% of coupling agent, 0.5-1 wt% of ultraviolet absorber, 0.2-0.4 wt% of antioxidant and 0.5-5 wt% of processing aid.

8. The integrated high barrier packaging material according to claim 5 or 7, characterized in that: The radiation auxiliary cross-linking agent includes one or more acrylate compounds containing multi-functional groups.

9. The integrated high barrier packaging material according to claim 1, characterized in that: The insulating support layer further comprises the following components, calculated according to the proportion of the resin system of the layer: 0.8-1.5 wt % of ultraviolet absorber, 0.5-2 wt % of antioxidant and 0.5-3 wt % of processing aid.

10. A method for preparing the integrated high barrier packaging material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the raw material components of each layer respectively, adopting multi-layer integrated melt co-extrusion, wherein the extrusion temperature of the bonding packaging layer is 180-200°C, the extrusion temperature of the light management layer is 190-220°C, the extrusion temperature of the gas barrier layer is 180-220°C, the extrusion temperature of the mechanical transition layer is 180-220°C, and the extrusion temperature of the insulating support layer is 200-230°C; after extrusion, the material is cast and cooled, and then subjected to irradiation pre-crosslinking and post-treatment in sequence to obtain an integrated high-barrier packaging material.

Citation Information

Patent Citations

  • Solar cell packaging rubber film and preparation method thereof

    CN102863914A

  • High-barrier-property high-reflection backboard material for crystalline silicon photovoltaic assembly

    CN108504300A

  • Packaging integrated backboard and preparation method thereof

    CN109473498A

  • Packaging adhesive film and preparation method thereof

    CN111334200A

  • High-viscosity and high-water-resistance packaging adhesive film, preparation method thereof and heterojunction battery assembly

    CN116769425A